2021
DOI: 10.1016/j.jeconom.2019.08.015
|View full text |Cite
|
Sign up to set email alerts
|

An econometric model of network formation with an application to board interlocks between firms

Abstract: We study identification of the players' preferences in a network formation game featuring complete information, nonreciprocal links, and a spillover effect. We decompose the network formation game into local games such that the network formation game is in equilibrium if and only if each local game is in equilibrium. This decomposition helps us prove equilibrium existence, reduce the number of moment inequalities characterising the identified set, and simplify the calculation of the integrals entering those mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…As with the example of pure strategy Nash equilibrium, this can be used to derive a partial identification result for the utility functions (for more on these solution concepts, see, e.g., Jackson 2010, chapter 6). Related partial identification results have been derived by Miyauchi (2016), de Paula et al (2018, Sheng (2020), andGualdani (2021).…”
Section: Multiple Decision Makersmentioning
confidence: 99%
“…As with the example of pure strategy Nash equilibrium, this can be used to derive a partial identification result for the utility functions (for more on these solution concepts, see, e.g., Jackson 2010, chapter 6). Related partial identification results have been derived by Miyauchi (2016), de Paula et al (2018, Sheng (2020), andGualdani (2021).…”
Section: Multiple Decision Makersmentioning
confidence: 99%
“…To avoid this difficulty, a large part of the literature has been trying to provide a confidence region for an outer set , that is, a collection of values for the parameter of interest that contains the identified set but may also contain additional values 1 . Because of its tractability, constructing a confidence region for an outer set has been entertained in various topics of studies where the parameters of interest are only partially identified; see, for instance, Blundell, Gosling, Ichimura, and Meghir (2007), Ciliberto and Tamer (2009), Aucejo, Bugni, and Hotz (2017), Sheng (2020), De Paula, Richards‐Shubik, and Tamer (2018), Dickstein and Morales (2018), Honoré and Hu (2020), Chesher and Rosen (2020), Gualdani (2021), and Berry and Compiani (2023), among many others.…”
Section: Introductionmentioning
confidence: 99%
“… See, for instance, Sheng (2020), Gualdani (2021), and the empirical application in Berry and Compiani (2023, Section 6, footnote 42). …”
mentioning
confidence: 99%
“…Specifically, the model in equation ( 1) can be derived as a stable outcome in a static game. Papers that study the strategic formation of a network as a static game include Goldsmith-Pinkham and Imbens (2013); Leung (2015a,b); Menzel (2015); Miyauchi (2016); Boucher and Mourifié (2017); de Paula, Richards-Shubik, and Tamer (2017); Mele (2017); Candelaria and Ura (2018); Sheng (2018); Gualdani (2020), and Ridder and Sheng (2020). The authors study network formation models that account for network externalities.…”
Section: Introductionmentioning
confidence: 99%